Art Preservation Through Karang Taruna Empowerment in Mekar Jaya Village : A Case Study of Kompangan Arts and Traditional Dance - Waluyo, Hadi; Wahyuni, Anny (Future Science / FSH-PH Publications, 2023)
Indonesia is a country that is rich in culture which is the identity of a nation. One area that has its own culture is Jambi province with its Kompangan culture and traditional dances. However, the rapid development of digitalization has forced the Kompangan culture and traditional dance to be pushed aside. Especially among the youth who are currently more interested in foreign cultures that enter Jambi. Therefore, we need a container that is able to develop and preserve this culture. At this writing using a descriptive qualitative approach with data collection techniques carried out by observation, interviews, documentation and data validation. From the interview, an answer was found for the problems faced by culture in the village of Mekar Jaya by creating an art gallery through the empowerment of Karang Taruna Mekar Jaya. This studio will later conduct training on Kompangan art and Tri art traditionally every week. It is hoped that the existence of this studio can raise awareness to preserve Kompangan arts and dance arts and can foster a sense of pride in the culture that belongs to the village of Mekar Jaya.